Zircon U-Pb age and Hf isotope of Quanyishang A-type granite in Yichang： Signification for the Yangtze continental cratonization in Paleoproterozoic - Xiong, Qing; Zheng, JianPing; Yu, ChunMei; Su, YuPing; Tang, HuaYun; Zhang, ZhiHai (Chinese science bulletin, 2009)
Zircon U-Pb age and Hf isotope, and major and trace element compositions were reported for granite st Quanyishang, which intruded into the Kongling complex in Yichang, Hubei Province. The results show that the Quanyishang granite is rich in silicon and alkalis but poor in calcium and magnesium, and displays enrichment in Ga, Y, Zr, Nb but depletion in Sr and Ba, exhibiting the post-orogenic A-type affinity. 90% zircons from the granite are concordant, and give a middle Paleoproterozoic magmatic crystallization age （mean 1854 Ma）. Initial Hf isotope ratios （^176Hf/^177Hf）i of the middle Paleoproterozoic zircons range from 0.280863 to 0.281134 and they have negative εHf（t） values with a minimum of -26.3. These zircons give the depleted mantle model ages （TOM） of 2.9-3.3 Ga （mean 3.0 Ga）, and the average crustal model ages （Tcrust） of 3.6-4.2 Ga （mean 3.8 Ga）., A Mesoarchean grain with ^207Pb/^206Pb age of 2859 Ma has a slightly high TOM （3.4 Ga） but similar Tcrust （3.8 Ga） to the Paleoproterozoic zircons. All these data suggest that the source materials of the Quanyishang A-type granite are unusually old, at least ≥2.9 Ga （even Eoarchean）. The event of crustal remeiting, which resulted in the formation of the Quanyishang granite in the middle Paleoproterozoic, recorded the cratonization of the Yangtze continent. The process may have relation to the extension and collapse of the deep crust with Archean ages, in response to the transition stage of the assembly and breakup of the Columbia supercontinent.